Developing Comic Strip-Based Learning Media For Writing Assignments - Nuriyah Welia Purnama Sari; Istiqamah Ardila; M Saufi Rahman (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This research aims to develop comic strip as a media learning focused on improving the writing skills of seventh-grade students at MTsN 3 HSU. This media is designed to address issues found during the initial observation, such as students' low interest in writing, limited vocabulary, and difficulty understanding English sentence structures. The development of this media adopts the Research and Development (R&D) model proposed by Borg and Gall, with stages that include needs analysis, planning, development of the initial product, expert validation, initial trial, product revision, main field trial, and final revision. The developed media contains comics with an engaging adventure storyline, characters that match the students' characteristics, and is accompanied by writing tasks that train vocabulary usage, basic grammar, and sentence construction skills. The results of validation from media and material experts show that the developed comic strip meets the "worthy" criteria as a learning media. The initial trial, which involved a small group of students, demonstrated that this media was able to attract students' interest, make it easier for them to understand writing material, and improve their ability to construct good sentences. The main field trial conducted with a larger group of students showed a significant improvement in the students' writing skills, including idea development, the use of more varied vocabulary, and better grammar understanding. In addition, students gave positive responses to the visually appealing design, easily understandable characters, and tasks that were challenging yet enjoyable.This study concludes that comic strip-based learning media is an effective and innovative alternative to improve the writing skills of seventh-grade students at MTsN 3 HSU. This media not only helps students improve their writing skills but also fosters higher learning motivation through an engaging visual and narrative approach. Therefore, the use of comic strips as learning media is recommended for implementation in English writing instruction at the junior high school level.